Psychometric properties of the survey work-home interaction nijmegen in Argentinian population - Colasanti, Elena Lucía; Castellano, Estanislao; Lapuente, Lucas; Moretti, Luciana Sofía; Medrano, Leonardo Adrián (Frontiers in Psychology, 2022)
Frictions between work and family life have increased during the COVID-19 pandemic, causing negative consequences on the mental health and quality of life of workers. Without validated instruments, it is not possible to determine the impact of Work-Family and Family-Work conflict. To date, no studies have been conducted to provide evidence of the validity and reliability of The Survey Work-Home Interaction Nijmegen (SWING; 22 items) in the population of Argentine workers. The SWING was administered to 611 Argentine workers of both sexes (73.6% female) aged between 18 and 70 years (M = 35.33; SD = 9.16) selected from a non-probabilistic accidental sampling. The confirmatory factor analysis showed satisfactory fit indices of the original four-factor model (χ2 = 647.073, gl = 203, CFI = 0.93, GFI = 0.92, NFI = 0.90, TLI = 0.92, RMSEA = 0.05, SRMR = 0.05, AIC = 557.9, BIC = 821.5). The level of reliability was acceptable (α between 0.68 and 0.86, ω = 0.79–0.89). The relationships of the subscale scores with the engagement and burnout variables were as expected according to previous studies. Having an instrument adequately adapted to the population of Argentine workers facilitates the development of studies aimed at evaluating the role of W-F or F-W interactions and their implications for health and productivity.